Creep fatigue behaviour of Type 321 stainless steel at 650°C. (November 2014) - Spindler, M. W.; Knowles, G.; Jacques, S.; Austin, C.
Abstract : Type 321 austenitic stainless steel has been used in the UK's advanced gas cooled reactors for a wide variety of thin section components which are within the concrete pressure vessel. These components operate at typically 650°C and experience very low primary stresses. However, temperature cycling can give rise to a creep fatigue loading and the life assessment of these cycles is calculated using the R5 procedure. In order to provide materials property models and to validate creep fatigue damage predictions, the available uniaxial creep, fatigue and creep fatigue data for Type 321 have been collated and analysed. The analyses of these data have provided evolutionary models for the cyclic stress strain and the stress relaxation behaviour of Type 321 at 650°C. In addition, different methods for predicting creep fatigue damage have been compared and it has been found that the stress modified ductility exhaustion approach for calculating creep damage gave the most reliable predictions of failure in the uniaxial creep fatigue tests. Following this, validation of the new R5 methods for calculating creep and fatigue damage in weldments has been provided using the results of reversed bend fatigue and creep fatigue tests on Type 321 welded plates at 650°C in conjunction with the materials properties that were determined from the uniaxial test data.